Recognition of isolated commands using the voice. - SOMIB, SOMIB (Revista Mexicana de Ingenieria Biomedica, 1991)
Nowadays, due mainly to the extraordinary technological progress that has taken place in the fields of electronics and computers, it is possible to carry out projects that man had previously conceived only as fantasies. This is the case of computer-based command recognition systems, capable of recognizing isolated words, taken from a pre-established vocabulary, in an automatic way. Before analyzing in detail, the way in which the computer performs the recognition, it is pertinent to mention some of the characteristics of the human voice. Voice generation is a physical process that seems so natural that we rarely think about how it is produced. If you consider all the mechanisms of human body involved in this process we would realize that it is a very complex mechanical process that involves the coordinated interaction of lungs, throat, vocal cords, trachea, nose and tongue. For each sound that is emitted, the brain coordinates all these organs and usually does so in an automatic way. The voice produces a current of air that leaves the lungs. The lungs retain about three-fourths of their capacity inside with air, and the diaphragm can send controlled amounts of air at a certain time and in a precise amount to the throat.